Early Warning Systems for Financial Crises.A Critical Approach - Stanislav Percic; Constantin-Marius Apostoaie; Vasile Cocris (CES Working Papers, 2013)
This research paper aims to analyse some Early Warning Systems (EWS) for predicting financial crises. The importance of such a study is undeniable in the context of the current and future mix of policies applied by the monetary authority, in which financial stability and price stability play an important role. The EWS for crises enable the prediction of the occurrence of a crisis within a specified time period. Hence, the theoretical approach of the main early warning systems for crises, the models based on signal extraction and the logit/probit models represent an important stage in preventing and fighting financial crises.
Keywords: E44; E47; F31; F47; G01; 330; financial crisis; currency crisis; Early Warning System; signal extraction; crisis prediction Romania